The regulation of Krox-20 expression reveals important steps in the control of peripheral glial cell development. - MURPHY, PAULA (Company of Biologists, 1996)
The zinc finger transcription factor gene Krox-20 is expressed in Schwann cells and is required for the myelination of peripheral nerves. We show that the regulation of Krox-20 expression in peripheral glial cells reveals three important steps in the development and differentiation of these cells. (i) Expression of Krox-20 in Schwann cells requires continuous neuronal signalling via direct axonal contact. Therefore Krox-20 appears to be a key component of the transduction cascade linking axonal signalling to myelination. (ii) Krox-20 inducibility is acquired by Schwann cells at the time that they are formed from their precursors. Diffusible factor(s) synthesised by the neural tube can mediate this transition and can be mimicked by NDFb or a combination of CNTF and bFGF. Furthermore, the neural tube activity is blocked by a hybrid protein containing the NDF-binding domain of the ErbB4 receptor, strongly implicating NDF in the physiological transition. (iii) In sensory ganglia, the microenvironment is capable of negatively regulating Krox-20, presumably by preventing the conversion of satellite glial cells toward a Schwann celllike phenotype.
PUBLISHED
Keywords: Schwann cell; satelite cell; myelin; Krox-20